STEAM Approach With Loose Parts Learning Materials In The Early Childhood Education - Ismaniar Ismaniar; Salsabila Deona; Klara Septia Landa (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2023)
The development of a very fast and competitive era demands the readiness of high quality and tough human resources. The use of the STEAM approach with Loose Parts learning materials is one of the unique learning at this institution, where the institution incorporates elements of local wisdom in STEAM and Loose Parts. The purpose of this study was to determine the institution's strategy in providing learning media used in implementing the Hauriyah Halum Integrated STEAM PAUD approach. This type of research is a case study with a qualitative approach and data collection techniques are carried out by means of interviews, observation and documentation. Data analysis techniques and data interpretation were carried out including; data reduction, data presentation and conclusion. While for the validity of the data is done by triangulation of methods and sources. The results of the study show that in carrying out learning activities with STEAM and Loose Part, the school utilizes the media in the environment around the child by adhering to the concept of